Dystonia and Partial Cytochrome B Deficiency - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1991)
An 18 year old female with idiopathic torsion dystonia associated with mitochondrial encephalomyopathy is reported from the Departments of Neurology, Pediatrics and Biochemistry, Wayne State University School of Medicine, Detroit, Michigan.